RESTRUKTURISASI UTANG PT GARUDA INDONESIA, Tbk. SEBAGAI UPAYA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG KEPADA KREDITUR - Widya Sari Amalia; Iswi Hariyani; Bhim Prakoso (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2022)
PKPU has a goal to improve the company from an economic standpoint and the company's ability as a debtor to make a profit, with this step it is hoped that the company can pay off its obligations. Settlement is not defined by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (hereinafter referred to as the Bankruptcy Law and PKPU). However, in this case the general understanding is as normalized in Article 222 of the Bankruptcy Law and PKPU that in principle the reconciliation plan includes an offer to pay part or all of the debt to creditors. In bankruptcy and PKPU cases, all creditors and debtors have the opportunity to submit a peace plan which can be part of a debt restructuring. SOEs have a responsibility in the problems being faced by PT Garuda Indonesia, Tbk. PT Garuda Indonesia, Tbk. is unable to pay its debts to creditors because of the equity of PT Garuda Indonesia,Tbk. recorded negative. The enormous debt made PT Garuda Indonesia, Tbk. choose to do debt restructuring even though the path chosen has a risk of bankruptcy. Even though PT Garuda Indonesia, Tbk. is experiencing financial problems. continue to run its business, this is in line with the principle of business continuity as normalized in 240 of the Bankruptcy Law and PKPU.